Sistem Informasi Manajemen Aset Dinas Komunikasi Dan Informatika - Pernanda, Rizal; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2023)
The Jambi City Communication and Informatics Service is an agency engaged in communication, informatics, coding, and also statistics for the city of Jambi. This agency has assets that can be said to be in large quantities, but in management, it is still carried out in a way where the financial staff who manage the asset section will request reports from each head of the field who is responsible for what items have been purchased for needs. each of these fields. With that in mind, the purpose of the analysis and design of this asset management information system is to fulfill what has been intended for the future as the needs of system users and also provide an overview of the design that will be made. The method used in system design is the prototyping method. For system modeling tools used by the author are Use Case Diagrams, Activity Diagrams, Class Diagrams. The prototype of this asset management information system is expected in the future as an application design that will be created and implemented by the Jambi City Communication and Informatics Office.